Bantuan Hukum “Pro Bono Publico” Dalam Pemenuhan Hak Memperoleh Keadilan Dan Persamaan Di Muka Hukum Di Provinsi Jawa Timur - Susiani, Dina (Journal of Law and Administrative Science, 2023)
Abstract. Law enforcement in Indonesia is complex and not easy. Since the Legal Aid Law was passed in 2011, various hopes have begun to emerge for the development of a legal aid system that can be accessed by all groups of society, especially the poor (poor). However, along the way, there are still many weaknesses and need significant improvement. Therefore the problem is how to implement the provision of free legal aid (pro bono publico) by the local government for the poor in East Java province; as well as how the coordination between the Regional Government of East Java Province and the Regional Office of the Ministry of Law and Human Rights of East Java as providers of legal aid in the regions. This research method uses a qualitative approach that is descriptive. Then carried out a qualitative analysis of the substance and context of the research from the aspect of human rights. The practice of providing legal aid to the poor in East Java Province is still experiencing obstacles, including the lack of socialization regarding the provision of legal aid to the poor, the minimal number of Legal Aid Organizations (OBH) in providing legal aid, the amount of legal aid costs is insufficient in the process at the trial, as well as administrative requirements related to the Certificate of Disability (SKTM) which was misused by several individuals and did not match its purpose.